Structure Rearrangement of an Introductory Course for General Shipping Education (World Journal of Vocational Education and Training, 2021)
A literature on maritime education is at the corner side, comparing with large amount of works on business and management topics. However, the importance of forming and updating a maritime education system should not be neglected, leaving a research gap for academic discussion. This paper is a continuation of an introductory course design study in a maritime university (Wang, Zhang, Ge, & Chao, 2021). In the last paper, we deal with the content selection problem for general shipping education. The content of shipping education relies heavily on the practice. Evolved with the internal and external environment change of shipping industry, the structure of the course designed before cannot fully comply with the industrial requirements. This paper aims to rearrange the course structure by increasing the student and practitioner engagement, where the student preference and industrial requirements are both considered. The Entropy-TOPSIS model is applied to evaluate the contents of each module. It is shown that students and practitioners are very sensitive to the different modules; the common and divergent perspectives were identified. Finally, the proportion of each content was adjusted accordingly based on the results of the measurement. The main contribution is to provide a possible solution for the course reform of general shipping education.